Analisis Antropometri, Biomekanika, dan Beban Kerja Fisik pada Pengoperasian Alat Pengupas Nenas Tipe Engkol - Sri Hartuti; Zulfahrizal Zulfahrizal; Muhammad Dhafir; Muslim Muslim (Department of Agricultural Engineering, Syiah Kuala University, 2012)
This study aims to analyze anthropometry, biomechanics, and physical workload on the use of a crank-type pineapple peeler. The results showed that the crank-type pineapple peeler could be used at optimum hand reach. Based on the measurement results, the average heart rate for operators ranges from 101–112 pulses/minute, and it was classified as medium workload. The rate of oxygen consumption at the operator reached 0.67–0.89 liters/minute, and it could be classifiedas low workload.